Peranan Public Relations dalam Kegiatan Happy Selling untuk Mengelola Citra Positif (Studi Kasus : PT Bank Mandiri (Persero)Tbk - Vilbia, Eka Yona (LUGAS Jurnal Komunikasi, 2022)
Companies that already have a positive image in the eyes of the public but there are many customers and prospective customers who have not received information about the products being marketed so that the role of public relations is needed in providing information. The purpose of this study is to analyze the role of public relations in happy selling activities to manage a positive image at PT Bank Mandiri (Persero) Tbk West Jakarta as a company engaged in banking services in Indonesia. The concept used in this study is the concept of RosadyRuslan (2016). This research method uses descriptive qualitative method. Data collection techniques using observation techniques, in-depth interviews, literature studies both printed and online. The results of this study indicate that the role of Public Relations at PT. Bank Mandiri (Persero) Tbk West Jakarta uses the concept of the role of public relations as a communicator and relationship in managing a positive image, with various activities such as Happy Selling to become a bridge between customers and Bank Mandiri in delivering information - information about Bank Mandiri products. So far all activities implemented through happy selling activities have been carried out well so that a positive image remains well formed at PT. Bank Mandiri (Persero) Tbk West Jakarta.